PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TOBA - Pane, Vitria; Siagian, Nalom; Tobing, Artha Lumban (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to find out how the public perceives the service quality of the Toba Regency Population and Civil Registration Service (Study on Making E-KTP and KK). The method used in this research is descriptive qualitative while the number of informants is 11 people. This study uses data analysis techniques consisting of data reduction, data presentation and drawing conclusions. The results of the study show that the quality of public services in the Population and Civil Registration Office of Toba Regency seen from the tangible dimension (physical evidence) does not meet the quality of service properly, the Reliability dimension of employees has carried out in a timely manner according to applicable regulations and has standard procedures in carrying out the function as a service to the community so that it runs in a structured manner, the Responsiveness dimension means that employees have shown a responsive attitude to the community the officers will respond well and quickly, the Assurance dimension that guarantees certainty of service time and guarantees of service costs is good but not yet provide satisfaction to the community as service users, the last dimension, namely Empathy (Empathy) in providing services also behaves unfairly and is still indiscriminate (discriminatory). In accordance with the research that has been done, service officers at the Population Administration and Civil Registration Office of Toba Regency still discriminate between people who provide services